Prize sharing in collective contests - Shmuel Nitzan; Kaoru Ueda (Center for Economic Studies and ifo Institute (CESifo), 2010)
The characteristics of endogenously determined sharing rules and the group-size paradox are studied in a model of group contest with the following features: (i) The prize has mixed private-public good characteristics. (ii) Groups can differ in marginal cost of effort and their membership size. (iii) In each group the members decide how much effort to put without observing the sharing rules of the other groups. It is shown that endogenous determination of group sharing rules completely eliminates the group-size paradox, i.e. a larger group always attains a higher winning probability than a smaller group, unless the prize is purely private. In addition, an interesting pattern of equilibrium group sharing rules is revealed: the group attaining the lower winning probability is the one choosing the rule giving higher incentives to the members.
Keywords: 330; collective contest; mixed public-good prize; endogenous sharing rules; the group-size paradox; Gruppenarbeit; Extensives Spiel; Erfolgsbeteiligung; Öffentliches Gut; Ökonomischer Anreiz; Theorie